REDUCING WORK-RELATED MUSCLE PAIN THROUGH STRETCHING: A QUASI-EXPERIMENTAL COMMUNITY NURSING STUDY IN PASURUAN, INDONESIA - Ana, Karisma Dwi; Kusyani, Asri; Darsini, Darsini; Putra, Kusuma Wijaya Ridi (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Work-related muscle pain is a common health problem among beauty clinic workers due to prolonged standing and repetitive movements. Stretching exercises are recognized as a low-cost, non-pharmacological intervention for preventing and reducing musculoskeletal discomfort. This study aimed to evaluate and compare the effectiveness of supervised and unsupervised stretching programs in reducing muscle pain among beauty clinic workers.   Method: A quasi-experimental study employing a two-group pretest–posttest design was conducted with 84 participants recruited from two beauty clinics in Pasuruan, Indonesia. Participant selection was based on predetermined inclusion and exclusion criteria established by the researchers. At Clinic A, participants received supervised stretching exercises facilitated by a community health nurse, whereas at Clinic B, the same stretching routine was carried out independently using printed guidelines. Pain intensity was assessed using the Numeric Rating Scale (NRS) both before and after a two-week intervention period. Data analysis was performed with the Wilcoxon Signed-Rank Test and the Mann–Whitney U Test.   Result: Both groups experienced a significant reduction in muscle pain after the intervention (p < 0.001). However, Clinic A showed a greater improvement in pain reduction compared to Clinic B (p = 0.025), indicating the added benefit of professional supervision.   Conclusion: Stretching is an effective strategy for reducing work-related muscle pain, and supervision by community health nurses enhances its effectiveness. This finding supports the integration of structured stretching programs into workplace health promotion, particularly in service sectors with high physical demands. This highlights the vital role of community health nurses in workplace musculoskeletal prevention and the importance of integrating nurse-led initiatives into occupational health programs.   Keywords: Muscle pain, stretching exercise, workplace intervention, community health nursing; beauty clinic workers.